Transmission effects of the U.S. and China monetary policy shocks on the world. Issue 46 (2nd October 2019) - Chiang, Shu-Mei; Liu, Hung-Chun; Huang, Chien-Ming; Chen, Hsin-Fu
ABSTRACT: This paper applies the Markov-switching model to analyse the transition probabilities and generalized method of moments (GMM) with Newey–West heteroscedasticity and autocorrelation consistent covariance estimators (HAC) to examine the continuity of monetary policies in different countries when the U.S. and China change their monetary policies. Our results indicate that the euro area's monetary authority continues to increase/decrease their money supply to stimulate/depress the economy. In Japan, long-term economic recession motivated the Japanese government to maintain a loose money supply. The continuity of Korea's monetary policy in expansionary states lasts up to 5.1 years. Besides, the outcomes show the implementation of U.S. quantitative easing (QE), overnight reverse repurchase agreement (RRP), and Chinese RRP policies have significant spillover effects on other nations. Particularly, the effects on the euro area are the largest. Furthermore, although the monetary policies of China and the euro area seem to move in opposite directions, they are interdependent.